A comparative study of termination of student status in Central Europe - Demeter-Karászi Zsuzsanna; Pallay Katalin; Tóth Dorina Anna; Поллоі Каталін (Akadémiai Kiadó, 2019)
Abstract. If the student status ends before the absolutorium (pre-degree), we can speak about dropout. In our paper, we are going to present the cases of termination of the student status and we would also like to make a comparison in three countries: Hungary, Ukraine, and Romania. The aim of our research is to demonstrate the various ways in which student status can be terminated. The dropout is an important and significant topic in higher education policy, because it causes institutional and individual loss, too.
Keywords: dropout; student status; higher education policy